Restoration of severely decayed primary incisors using indirect composite resin restoration technique - C. MOTISUKI, L. SANTOS-PINTO & E. M. A. GIRO (Paediatric Dentistry, 2005)
Caries and trauma are the main reasons for the restoration of anterior teeth in young children.